A synthetic chalcone derivative, 2-hydroxy-3′, 5, 5′-trimethoxychalcone (DK-139), triggers reactive oxygen species-induced apoptosis independently of p53 in A549 lung cancer cells. (25th January 2019) - Gil, Ha Na; Jung, Euitaek; Koh, Dongsoo; Lim, Yoongho; Lee, Young Han; Shin, Soon Young
Abstract: 2-Hydroxy-3′, 5, 5′-trimethoxychalcone (named DK-139) is a synthetic chalcone derivative that has anti-inflammatory, anti-tumor, and endoplasmic reticulum-mediated apoptosis activities. However, the mode of action of DK-139 on reactive oxygen species (ROS)-induced apoptosis remains unknown. In this study, we found that DK-139 activated DNA damage responses, as was revealed by the accumulation of the tumor suppressor p53 and the phosphorylation of histone H2AX at Ser139 (called γ-H2AX), which are hallmarks of DNA damage responses. The occurrence of DK-139-induced DNA damage was confirmed through single-cell gel electrophoresis (comet tail assay). Interestingly, using p53-null HCT116 cells revealed that p53 was not involved in DK-139-induced apoptosis. Instead, we found that DK-139 increased the production of ROS, which led to the processing of caspase-2, BH3 interacting-domain death agonist (BID), caspase-9, and caspase-7. Pretreatment with the ROS scavenger N-acetyl cysteine reduced the frequency of DK-139-induced γ-H2AX formation, demonstrating that DK-139 triggered DNA damage through ROS production. In addition, NAC pretreatment prevented DK-139-induced processing of caspase-2, BID, caspase-9, caspase-7, and poly(ADP-ribose) polymerase. These results suggest that DK-139 triggers apoptosis through ROS-mediated DNA damage and activation of the caspase-2 cascade in A549 human lung cancer cells. Graphical abstract: Highlights: DK-139 is a synthetic trimethoxychalcone derivative. DK-139 inhibits A549 non-small cell lung cancer cell growth. DK-139 induces DNA damage. DK-139 triggers ROS-induced apoptosis. DK-139 may be used as an anticancer agent against non-small cell lung cancer cells.